2021
DOI: 10.3390/biomedicines9101305
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Gut Microbiota and Complications in Gastrointestinal-Cancer Therapies

Abstract: The therapy of gastrointestinal carcinomas includes surgery, chemo- or immunotherapy, and radiation with diverse complications such as surgical-site infection and enteritis. In recent years, the microbiome’s influence on different diseases and complications has been studied in more detail using methods such as next-generation sequencing. Due to the relatively simple collectivisation, the gut microbiome is the best-studied so far. While certain bacteria are sometimes associated with one particular complication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
0
5
1
Order By: Relevance
“…Although we did not show any statistical significance, some previous studies reported important changes in the composition of the intestinal microbiota after undergoing colorectal surgery [ 5 ]. A previous study showed that reduced alpha diversity was associated with the incidence of postoperative complications [ 23 ].…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Although we did not show any statistical significance, some previous studies reported important changes in the composition of the intestinal microbiota after undergoing colorectal surgery [ 5 ]. A previous study showed that reduced alpha diversity was associated with the incidence of postoperative complications [ 23 ].…”
Section: Discussioncontrasting
confidence: 94%
“…A previous study showed that reduced alpha diversity was associated with the incidence of postoperative complications [ 23 ]. A higher abundance of specific bacteria, such as Bacteroidaceae , Bifidobacterium genus, and Enterococcus faecalis, may be associated with an increased risk of anastomotic leakage [ 2 5 24 ]. In addition, the Firmicutes / Bacteroidetes ratio can be altered during colorectal cancer surgery, which may represent dysbiosis of the intestinal microbiota and can be associated with poor outcomes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between microbial dysbiosis, chronic inflammation, immune evasion and oxidative stress has already been reported for Helicobacter pylori in gastric tumors and for F. nucleatum in CRC [ 99 , 100 ]. Despite the bond between skin microbiota, ROS and NMSC occurrence is still largely unknown, the state of dysbiosis, which causes a greater susceptibility to exogenous and non-exogenous stimuli, also favors DNA damage, such as the formation of thymine dimers and C-T transitions, erythema, immunosuppression, melanogenesis, photo-ageing and cancer [ 101 , 102 ].…”
Section: Microbiota and Skin Cancermentioning
confidence: 98%